The Role of Pancasila in Facing the Challenges of Globalization - Dino Ardiansyah Putra; Geraldo Ghazian Putra Prakoso (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
In Indonesia, in social and state life, Pancasila functions as a basic ideology that guides the direction of state administration. By practicing the values ​​of life based on Pancasila, Pancasila becomes the normative foundation that regulates how Indonesian society realizes national and state life in accordance with national goals. As time goes by, the impact of globalization and modernization can be seen in social and state life. To filter out external cultural influences, Pancasila is needed as an official guideline and instrument for assessing and critiquing the influence of industrialization and globalization. Various norms demonstrate how each value within the Pancasila principles is implemented. As an archipelagic nation with diverse races, ethnicities, religions, and cultures, Indonesia places Pancasila as a crucial element in maintaining the unity of the Indonesian people and thus serving as a reference and guideline in social and state life. Globalization, as a form of social change that transcends national borders, is indeed unavoidable. While it offers easy access and connectivity without the limitations of space and time, globalization also brings challenges for the younger generation, who have the potential to lose their national identity due to the rapid pace of globalization.